FORM OF PRESENTATION AND SHIFT FUNCTION OF DODOD ANGKLUNG ART IN PAMATANG VILLAGE, MEKARWANGI VILLAGE, SAKETI SUB-DISTRICT, PANDEGLANG REGENCY - Ardiansyah Nugraha; Rian Permana; Suhaya Suhaya (MATRA: Jurnal Seni Musik Tari Teater & Rupa, 2023)
Dodod angklung is one of the traditional arts of Pandeglang, this art arose because the past farming community created an art from the lives of farmers. The name dodod anklung is taken based on the musical instruments used, namely dodod and angklung, this art developed in the Banten area, to be precise, in Pamatang Village, Mekarwangi Village, Saketi District, there is a Sanghiang Sri dodod angklung group whose existence is still known by the public. This research is included in qualitative research, namely research that provides an overview of the conditions or symptoms that occur without leaving the object under study. In this study, researchers used qualitative research methods. Dodod and also angklung consisting of dodod indung, dodod turulung, dodod percussion, angklung indung, angklung percussion, angklung turulung, angklung goong, angklung goong 2, angklung enclok 1, angklung enclok 2, and angklung nying each instrument has a sound In the beginning, the art of dodod angklung in Pamatang village had a sacred function because it was used by the people in the past to perform rituals related to agriculture, the ritual consisted of the rituals of tatanen, ngalaksa, and apostles.  FORM OF PRESENTATION AND SHIFT FUNCTION OF DODOD ANGKLUNG ART IN PAMATANG VILLAGE, MEKARWANGI VILLAGE, SAKETI SUB-DISTRICT, PANDEGLANG REGENCY